2007
DOI: 10.1007/s11932-007-0072-1
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary problems in bicyclists

Abstract: Genitourinary complaints are common in cyclists. Bicycle fit, improper saddle type, and individual anatomic factors are important evaluation criteria to consider when diagnosing symptoms and determining treatment options. By learning how to recognize and treat contributing factors, as well as learning a few simple bike-fitting techniques, physicians can treat and prevent many common problems associated with bicycling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…16 A standard saddle is designed so that the rear wide portion supports the ischial tuberosities, whereas the front narrow portion is designed to help the rider control the bike with the thighs. 17 Other functions of the nose include limiting side-to-side rocking of the bicycle, providing support at high speeds or over rough terrain, enabling more efficient steering, providing stability by preventing cyclists from falling off the saddle, and repositioning when pedaling and giving comfort as a result of control and balance. 18 The Hypothesis Suggestion of high prevalence of genital numbness and/or ED in the epidemiologic literature has led to the association of bicycling with ED.…”
Section: Pathophysiologymentioning
confidence: 99%
“…16 A standard saddle is designed so that the rear wide portion supports the ischial tuberosities, whereas the front narrow portion is designed to help the rider control the bike with the thighs. 17 Other functions of the nose include limiting side-to-side rocking of the bicycle, providing support at high speeds or over rough terrain, enabling more efficient steering, providing stability by preventing cyclists from falling off the saddle, and repositioning when pedaling and giving comfort as a result of control and balance. 18 The Hypothesis Suggestion of high prevalence of genital numbness and/or ED in the epidemiologic literature has led to the association of bicycling with ED.…”
Section: Pathophysiologymentioning
confidence: 99%
“…While genitourinary complaints have been well studied in cyclists [ 7 ], the negative effects of the cyclist's physical position and the resultant perineal hypoperfusion should be relatively obvious. Certain studies have also reported up to 30% of athletes being diagnosed with varicocele, representing a significantly higher incidence than in the general population, and up to 60–80% of body-builders are recorded as being affected.…”
Section: Introductionmentioning
confidence: 99%
“…6 It has been reported that 7-8% of cyclists on long-distance multi-day rides experience pudendal neuralgia, described as severe, sharp pain along the course of the pudendal nerve. 49 In men, pain can affect the perineum, scrotum, anus and penis. The pain can be unilateral or bilateral.…”
Section: Effect Of Cycling On Soft-tissue Perineal Lesions ('Cyclist ...mentioning
confidence: 99%